Reinventing Religious Studies Key Writings in the History of a Discipline. - Elliott, Scott S. (London ; New York : Routledge, 2014)
""Reinventing Religious Studies"" offers readers an opportunity to trace the important trends and developments in Religious Studies over the last forty years. Over this time the study of religion has been transformed into a critical discipline informed by a wide range of perspectives from sociology to anthropology, politics to material culture, and economics to cultural theory. ""Reinventing Religious Studies"" brings together key writings which have helped shape scholarship, teaching and learning in the field. All the essays are drawn from the CSSR Bulletin, a provocative, occasionally irreve.
30. Response to Raymond B. Williams's "So, what are we professing here? Religion, the liberal arts, and civic life"31. Response to Raymond B. Williams's "So, what are we professing here? Religion, the liberal arts, and civic life"; 32. Rejoinder; Part VI: Religious studies and identity politics; 33. Late capitalism arrives on campus: making and remaking the study of religion; 34. Religious studies and identity politics: mythology in the making; 35. Toward an engaged religious studies; 36. The study of religion under late capitalism, or commodity triumphant; Part VII: Islam and 9/11
Description based upon print version of record.
Includes bibliographical references and index.
37. On the teaching of Islam in America
Keywords: Religion -- Methodology; Religion -- Study and teaching; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Religion -- Study and teaching -- History; Manners and customs; Social history; Religious literature -- History and criticism; Electronic books